Effect Of Implementation Of Cooperative Learning Model Make A Match Technique On Student Learning Motivation In Social Science Learning - Nur Fidiyanti, Hana Hartanti (International Journal Pedagogy of Social Studies, 2017)
The problem in this study is the low motivation to learn social science in students class VIII. Those are based on the observation that teachers have not applied varied learning models and tend to use conventional learning method. Learning activities have not actively involved students and many tudents feel bored in social science learning. Teachers need to overcome these problems by applying creative learning model, fun and can foster students#39; learning motivation, one of them is cooperative learning model of make a match technique. This study aims to determine the effect of cooperative learning model of make a match technique to the motivation of social science learning in students class VIII SMP Negeri 40 Bandung. The design of this study uses Nonequivalent Control Group Design with quasi experimental research method. The samples of this study are 60 students and using 2 classes,namely class VIII D as experiment class and class VIII C as control class. Data were analyzed by using SPSS 17.00 for windows.Â  The results showed that: First, the learning motivation of students before and after implementing cooperative learning model of make a match technique increased but still low category. Second, the students#39; learning motivation before and after implementing conventional method did not increase. Third, simultaneously learning motivation between students who learn with cooperative learning model of make a match technique is better than students who learn with conventional learning method.